2‐Carbaborane‐3‐phenyl‐1H‐indoles—Synthesis via McMurry Reaction and Cyclooxygenase (COX) Inhibition Activity. Issue 2 (9th January 2013) - Laube, Markus; Neumann, Wilma; Scholz, Matthias; Lönnecke, Peter; Crews, Brenda; Marnett, Lawrence J.; Pietzsch, Jens; Kniess, Torsten; Hey‐Hawkins, Evamarie
Abstract Cyclooxygenase‐2 (COX‐2) inhibitors have been the focus of medicinal chemistry efforts for years, and many compounds that exhibit high selectivity and affinity have been developed. As carbaboranes represent interesting pharmacophores as phenyl mimetics in drug development, this paper presents the synthesis of carbaboranyl derivatives of COX‐2‐selective 2, 3‐disubstituted indoles. Despite the lability of carbaboranes under reducing conditions, 2‐carbaborane‐3‐phenyl‐1H‐indoles could be synthesized by McMurry cyclization of the corresponding amides. Whereas the meta‐carbaboranyl‐substituted derivatives lacked COX inhibitory activity, an ortho‐carbaboranyl analogue was active, but showed a selectivity shift toward COX‐1.